Oxidation phenomena and color properties of grape pomace on nitrite-reduced meat emulsion systems. (November 2016) - Riazi, Fatemeh; Zeynali, Fariba; Hoseini, Ebrahim; Behmadi, Homa; Savadkoohi, Sobhan
Abstract: The present study focuses on the effect of different levels of red grape pomace (1 and 2%, w/w) on the color changes, lipid oxidation (TBARS), antioxidant activity, microbial counts, total phenol content and sensory attributes of the sausages formulated with various levels of sodium nitrite (30, 60 and 120 mg/kg). It was found that the addition of grape pomace (1%, w/w) in combination of reduced nitrite levels to the beef sausage samples reduced TBARS content and the degree of lipid oxidation. Antioxidant activity and total phenol contents were further evaluated based on DPPH scavenging activity method. A significant reduction in lightness ( L* ) and yellowness ( b* ) of systems containing grape pomace was observed, following by an increase in the oxidative stability and the radical scavenging activity. Acceptability of beef sausages was not significantly ( P  > 0.05) affected by the addition of grape pomace and had relatively greater scores from a sensory point of view. Highlights: Decreases in lipid oxidation values of sausages containing 1% grape pomace were observed. Lightness and yellowness of sausages were affected by level of grape pomace. Redness of nitrite-reduced sausages was significantly diminished by grape pomace level. Total phenol content was significantly affected by the amount of grape pomace. Grape pomace-added sausages had higher scores for taste and odor.